Metal–oxygen hybridization determined activity in spinel-based oxygen evolution catalysts : a case study of ZnFe2–xCrxO4 - Li, Haiyan (2020)
A good understanding of the correlation between electronic properties and catalytic performance is vital to the rational design of active oxygen evolution reaction (OER) catalysts. Here, a volcano-shaped correlation between the OER activity and the Cr substitution amount was found for spinel oxides ZnFe2–xCrxO4 (x = 0–2), in which Zn2+ resides in tetrahedral (Td) sites while Fe3+ and Cr3+ occupy octahedral (Oh) sites. Such a relationship probably is because Cr substitution tunes the eg occupancy of Oh-site transition metals (TMOh) via the Oh–Oh superexchange effect. Density functional calculations further revealed the hybridization degree between the TMOh 3d and the O 2p states, and a volcano-shaped trend was also found in the variation of TMOh 3d-O 2p hybridization with the amount of Cr substitution. The good correlation between the OER activity and the hybridization highlights the important role of metal–oxygen hybridization in determining the OER activity of these spinel oxides.